Competency level of parents of children with special needs in providing assistance for acquiring self-care skills - Tejano, Leonardo Daquioag (Universitas PGRI Madiun, 2023)
This research aimed to determine the competency level of parents of children with special needs in providing assistance for acquiring self-care skills, the challenges they face, and their demographic profile. The study utilized a descriptive research design, including both survey questionnaires and focus group discussions. The participants consisted of 50 parents of children with special needs, ages 7 to 14, residing in Ilocos Norte, Philippines. The results showed that mothers played a significant role in providing direct assistance to their children. Secondly, parents in the age group of 35-54 may face additional challenges in managing caregiving responsibilities. Moreover, parents with low levels of education and limited financial resources may face additional barriers in accessing resources to support their child's development. The competency assessment revealed that parents may need additional support in some areas, particularly in growth and development and toileting practices. The study recommends thatpolicymakers, educators, and healthcare professionals collaborate to create and implement programs that provide parents with the support and resources they need to care for their children. This research highlights the need for more support and resources for families of children with special needs.